(untitled) (The Review of Diabetic Studies, 2025)
Background: Kidney development involves morphological formation and functional maturation, beginning with embryonic nephron formation and continuing post-birth. Understanding renal structure and physiology is crucial due to the kidney’s vital roles in filtration, toxin susceptibility, and hormone production. This study aimed to examine the histological development of the kidney in various age groups using light and electron microscopy for detailed structural analysis. Materials and method: This study examined age-related renal changes in 30 white rats divided into three groups: two-month-old, four-month-old, and six-month-old rats. Kidneys were extracted after anaesthesia and dissected for analysis. Samples were preserved in 10% formalin for histological staining or prepared for electron microscopy. Results: The study revealed significant age-related changes in renal structure. Cortex thickness increased from 245.00±2.54 μm at 30 days to 287.00±2.33 μm at 6 months, while medulla thickness rose from 299.11±2.98 μm to 335.00±2.33 μm. Mesangial cell counts decreased from 7.36±0.02 to 5.45±0.00, and glomerular diameter enlarged from 47.31±0.11 μm to 57.17±0.06 μm. Conversely, Bowman’s capsule diameter shrank from 12.65±0.06 μm to 8.43±0.06 μm, and proximal tubules decreased from 27.32±0.08 μm to 22.12±0.10 μm, with distal tubules showing minimal change. Electron microscopy indicated a significant glomerular size increase (10.8-fold) between two and six months, suggesting growth continued beyond four months, unlike in humans where stabilization occurs earlier. Conclusion: These findings highlight ongoing renal maturation in mice, critical for experimental design and data interpretation. The study underscores species developmental patterns and their implications for research and clinical applications.